Assessing customer complaints behaviour towards services delivered in restaurant / Noorliza Zainol ... [et al.] - Zainol, Noorliza; Ahmad Rozali, Abdul Rahman; Razali, Muhammad Azli; Aizat Bashir, Muhammad Arif; Tazijan, Farina Nozakiah (Universiti Teknologi MARA, Pulau Pinang, 2014)
Complaint behaviour in restaurant service industry is remarkably known. This study empirically investigates the attitudes, causes to complaints in restaurants and most importantly the customer complaints behaviour in restaurant services. Personally administered questionnaire was used and through a series of analyses from frequencies, descriptive to inferential statistics, some useful insights or predictors on the issues of interest were obtained. The findings indicate that majority of the restaurant customers are clearly concerned about the services that they have experienced in restaurant thus disappointed services will usually turn out to be complaints.